Un inedito poemetto tardo-trecentesco: il «Fiore dei Conversi» (Carte Romanze, 2023)
Abstract: The aim of this work is to provide a general overview and an essay of critical edition of an unpublished and anonymous poem in refrained sonnets (372 poems) dating back to the end of the fourteenth century, and handed down by a single manuscript, the code Chigiano M.IV.99 (Vatican Apostolic Library). The first part of the contribution intends to expose the more relevant aspects of the poem, and its supposed historical and cultural context (§ 1); the second one focuses on the codicological description of the manuscript (§ 2), the narrative structure of the poem (§ 3) and its linguistic analysis, in order to establish its geographical provenance (§ 4). In conclusion, an illustration of the tabula of the manuscript is provided (§ 5).The article is followed by an example of critical edition of four sonnets, to show the textual connection that combines the different poems in a unique narrative structure.
Keywords: poem in refrained sonnets; otherwordly journey; Dante’s epigonism; medieval Umbria